Semaglutide ameliorates diabetes-associated cognitive dysfunction in mouse model of type 2 diabetes - Yan Zhu; Yi He; Hongyan Yang; Yanbo Gao; Yan Wang; Peiqing Liu; Mengjuan Zhang (PLoS ONE, 2025)
Background Type 2 diabetes mellitus (T2DM) is associated with cognitive dysfunction, which significantly impacts the quality of life. Semaglutide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has shown potential neuroprotective effects. This study investigates the efficacy of semaglutide in ameliorating cognitive dysfunction in a mouse model of T2DM. Methods Male C57BL/6J mice were fed a high-fat diet for four weeks and received a single intraperitoneal injection of streptozotocin (150 mg/kg) to induce T2DM. All mice were divided into four groups: control, diabetes control (T2DM), semaglutide treatment (semaglutide, 0.1 mg/kg) and dapagliflozin treatment (dapagliflozin 1 mg/kg). Cognitive function was assessed using the Morris water maze (MWM) test. Histomorphological analysis of hippocampal tissues was performed using H&E and Nissl staining. Immunofluorescence was used to assess LRP1 expression and apoptosis. Biochemical analyses measured oxidative stress markers (SOD, MDA) and inflammatory cytokines (IL-1β, IL-6, TNF-α, CRP). Results Semaglutide treatment significantly reduced blood glucose levels in diabetic mice. In the MWM test, semaglutide-treated mice showed reduced escape latencies, indicating improved spatial learning and memory. Histomorphological analysis revealed preserved neuronal structure in the hippocampus with reduced neuronal damage and apoptosis in the semaglutide-treated group. Immunofluorescence showed increased LRP1 expression and decreased apoptosis. Biochemical analyses indicated that semaglutide reduced oxidative stress and inflammatory markers, further supporting its neuroprotective effects. Conclusions Semaglutide effectively ameliorates cognitive dysfunction in T2DM mice, likely through mechanisms involving the reduction of oxidative stress, inflammation, and neuronal apoptosis. These findings suggest that semaglutide has potential as a therapeutic agent for managing diabetes-associated cognitive decline. Further research, including long-term studies and clinical trials, is necessary to validate these findings and explore the broader applicability of semaglutide in treating cognitive impairments in diabetic patients.